A single light-responsive sizer can control multiple-fission cycles in Chlamydomonas - Heldt, F; Tyson, J; Cross, F; Novák, B (Cold Spring Harbor Laboratory, 2019)
Proliferating cells need to coordinate cell division and growth to maintain size homeostasis. Any systematic deviation from a balance between growth and division results in progressive changes of cell size over subsequent generations. While most eukaryotic cells execute binary division after a mass doubling, the photosynthetic green alga Chlamydomonas can grow more than eight-fold during daytime before undergoing rapid cycles of DNA replication, mitosis and cell division at night, which produce up to 16 daughter cells. Here, we propose a mechanistic model for multiple fission and size control in Chlamydomonas . The model comprises a light-sensitive and size-dependent biochemical toggle switch that acts as a sizer and guards transitions into and exit from a phase of cell-division cycle oscillations. We show that this simple ‘sizer-oscillator’ arrangement reproduces the experimentally observed features of multiple-fission cycles and the response of Chlamydomonas cells to different light-dark regimes. Our model also makes testable predictions about the dynamical properties of the biochemical network that controls these features and about the network’s makeup. Collectively, these results provide a new perspective on the concept of a ‘commitment point’ during the growth of Chlamydomonas cells and hint at an intriguing continuity of cell-size control in different eukaryotic lineages. Graphical abstract G1-sizer and S/M-oscillator can give rise to multiple-fission cycles in Chlamydomonas Light-responsive bistable switch may guard transition between G1 and S/M-cycles Illumination increases S/M-entry threshold, causing multiple-fission cycles Dark shift lowers S/M-entry threshold, allowing small cells to commit to fewer divisions